Studi Komparatif Kadar Flavonoid Total Makroalga Caulerpa racemosa Asal Pantai Teluk Sepang Melalui Variasi Konsentrasi Pelarut Etanol - Ade Apriansyah; Dwi Kurnia Putri; Putri Mulia; Ikhsan; Delia Komala Sari (Jurnal Pharmacopoeia, 2026)
Sea grapes are members of the Caulerpaceae algae family that have a thallus-like structure, a structure that can form chains or branches, and have small grains that resemble grapes, hence the name sea grapes. Furthermore, various modern studies have shown that Caulerpa racemosa contains important secondary metabolites, especially flavonoid compounds.  Flavonoids are a group of phenolic compounds found in almost all parts of plants, especially in the outer layer of leaves and fruit skin. The purpose of this study was to determine the total flavonoid content of 70% and 96% ethanol extracts of sea grape plants found in Teluk Sepang Beach, Bengkulu City. The method used was UV-Vis spectrophotometry with an aluminum chloride (AlCl₃) complexation colorimetric approach. This technique is relatively easy, fast, highly sensitive, and can be successfully applied to various extracts derived from natural materials, producing reliable results if accompanied by method validation. Measurement of flavonoid levels using quercetin as a comparison at a maximum wavelength of 430 nm and obtained a linear regression equat ion y = 0.0096x + 0.0535 and R2 = 0.9729. The total flavonoid content of 70% ethanol extract was 12.6 ± 0.16 mg QE/g and 96% ethanol extract was 44,1 ± 0.29 mg QE/g. Based on the results of this study, it can be concluded that 96% ethanol extract has a greater flavonoid content than 70% ethanol extract. Statistical analysis using the independent sample t-test confirmed a significant difference between the two treatments (p<0.05). This study concluded that 96% ethanol is a more effective solvent for extracting flavonoid compounds from Caulerpa racemosa than 70% ethanol, this shows that the difference does not occur by chance, but is a real effect of the difference in ethanol concentration in extraction.